Genetic diversity analysis of rice landraces (Oryza sativa L.) for salt tolerance using SSR markers in Bangladesh - Rashid, Md Mamunur; Imran, Shahin; Islam, Md Ashraful; Hassan, Lutful (Fundamental and Applied Agriculture, 2018)
Large cultivable area lies in the costal saline zone of Bangladesh where rice cultivation is largely affected by the salinity. This problem can be effectively addressed by identifying salt-tolerant landraces using modern biotechnolog- ical method. Assessment of genetic diversity of rice (Oryza sativa L.) is an important tool for rice breeding and an essential component in germplasm characterization and conservation. The objective of this study was to assess the genetic diversity among 7 landraces along with 3 released variety of rice using SSR marker. A total of 31 reproducible polymorphic alleles were identified from the loci with an average of 5.167 alleles per locus (ranges from 4–7). The polymorphism information content (PIC) value is a reflection of allelic diversity and frequency among the varieties. PIC value of each marker was evaluated on the basis of the number of alleles and it varied greatly for all the SSR loci tested. PIC values enumerated from the data obtained from allelic variation from 0.595 (RM8094) to 0.797 (AP3206) with an average of 0.697. The average genetic diversity over all SSR loci for the 10 genotypes was 0.740, ranging from 0.660 to 0.820. Positive correlations were found between gene diversity, PIC value and number of allele. These findings can have the potential role for further improvement of salinity tolerance rice genotypes through marker-assisted breeding. Keywords: Rice, genetic diversity, salt tolerance, PIC, SSR